Magnetically steered cell therapy for reduction of intraocular pressure as a treatment strategy for open-angle glaucoma - M Reza Bahranifard; Jessica Chan; A Thomas Read; Guorong Li; Lin Cheng; Babak N Safa; Seyed Mohammad Siadat; Anamik Jhunjhunwala; Hans E Grossniklaus; Stanislav Y Emelianov; W Daniel Stamer; Markus H Kuehn; et al. (eLife, 2025)
Trabecular meshwork (TM) cell therapy has been proposed as a next-generation treatment for elevated intraocular pressure (IOP) in glaucoma, the most common cause of irreversible blindness. Using a magnetic cell steering technique with excellent efficiency and tissue-specific targeting, we delivered two types of cells into a mouse model of glaucoma: either human adipose-derived mesenchymal stem cells (hAMSCs) or induced pluripotent cell derivatives (iPSC-TM cells). We observed a 4.5 [3.1, 6.0] mmHg or 27% reduction in intraocular pressure (IOP) for 9 months after a single dose of only 1500 magnetically steered hAMSCs, explained by increased outflow through the conventional pathway and associated with a higher TM cellularity. iPSC-TM cells were also effective, but less so, showing only a 1.9 [0.4, 3.3] mmHg or 13% IOP reduction and increased risk of tumorigenicity. In both cases, injected cells remained detectable in the iridocorneal angle 3 weeks post-transplantation. Based on the locations of the delivered cells, the mechanism of IOP lowering is most likely paracrine signaling. We conclude that magnetically steered hAMSC cell therapy has potential for long-term treatment of ocular hypertension in glaucoma.